Danggui-Shaoyao-San Improves Learning and Memory in Female SAMP8 via Modulation of Estradiol. (16th March 2014) - Huang, Yan; Hu, Zeng-yao; Yuan, Hui; Shu, Lei; Liu, Gang; Qiao, Shan-yi; Sun, Lei; Zhou, Wen-xia; Zhang, Yong-xiang
Abstract : Previous studies showed that Danggui-Shaoyao-San (DSS), a traditional Chinese medicinal prescription, could alleviate cognitive dysfunction of Alzheimer's disease (AD) patients. However, the mechanisms remain unclear; we have now examined the effect of DSS on SAMP8 and elucidated the possible mechanism. Animals were treated with DSS for 2 months, and step-down test and Morris water maze (MWM) test were used to evaluated cognitive abilities. The estradiol (E2), NO, and glycine in blood plasma or in hippocampus were detected to explore the possible mechanisms. The latency of SAMP8 in step-down test was shorter than that of age-matched SAMR1, and DSS increased the latency especially in female animals. In MWM test, we got similar results; SAMP8 spent more time to find the platform, and DSS decreased the time before finding the platform, with little effect on swim velocity, during the training sessions. During test session, DSS increased the time spent in target quadrant especially in female SAMP8. In female SAMP8, plasma E2, NO, and glycine were elevated in plasma or hippocampus tissue. In conclusion, DSS could ameliorate deterioration of cognition in SAMP8, especially in female animals. Increasing E2, NO, and glycine might contribute to the cognitive improvement effect of DSS in female SAMP8.